Kesavananda Bharati case: the untold story of struggle for supremacy by Supreme Court and Parliament - Andhyarujina, T. R. (New Delhi, 2013)
This book recounts the tensions and conflicts in the Kesavananda Bharati case not only between the rival sides but also amongst the judges, some of whom had preconceived views because of being judges in the earlier cases and others by reason of their selection by Government. The acrimony over the proposal to exclude Justice M.H. Beg who was in favour of Parliament by the Chief Justice and the Petitioners from the bench on his hospitalization almost at the end of the oral hearing is related as is the controversy over whether Justice Y.V. Chandrachud was prevailed upon to change his opinion against Parliament.
Keywords: "Kesavananda Bharati, Swami"